Biologic Agents for Periodontal Regeneration and Implant Site Development. (5th October 2015) - Suárez-López del Amo, Fernando; Monje, Alberto; Padial-Molina, Miguel; Tang, ZhiHui; Wang, Hom-Lay
Abstract : The advancement of molecular mediators or biologic agents has increased tremendously during the last decade in periodontology and dental implantology. Implant site development and reconstruction of the lost periodontium represent main fields in which these molecular mediators have been employed and investigated. Different growth factors trigger different reactions in the tissues of the periodontium at various cellular levels. Proliferation, migration, and differentiation constitute the main target areas of these molecular mediators. It was the purpose of this comprehensive review to describe the origin and rationale, evidence, and the most current understanding of the following biologic agents: Recombinant Human Platelet-Derived Growth Factor-BB (rhPDGF-BB), Enamel Matrix Derivate (EMD), Platelet-Rich Plasma (PRP) and Platelet-Rich Fibrin (PRF), Recombinant Human Fibroblast Growth Factor-2 (rhFGF-2), Bone Morphogenic Proteins (BMPs, BMP-2 and BMP-7), Teriparatide PTH, and Growth Differential Factor-5 (GDF-5).